Efektivitas Pembelajaran Metode Daring Pada Kegiatan Praktikum Di Fakultas Kedokteran Universitas Muslim Indonesia - Julian Muhammad Yasin; Syamsu Rijal; Edward Pandu Wiriansya; Sri Julyani; Shofiyah Latief (Universitas Muslim Indonesia, 2023)
Effectiveness generally shows the extent to which learning targets have been achieved. Effectiveness is a scale that shows the range of targets (quality, quantity and period) that have been achieved, and the greater the percentage of targets achieved, the greater the effectiveness. The change in learning methods due to the Covid-19 pandemic, was originally the face-to-face method changed to an online method which had more impact on the learning stage of students, especially medical students. For the Faculty of Medicine's curriculum which claims not only lectures, but along with practicum and clinical expertise that needs hands-on, so the change in method will definitely have an impact on student learning motivation. This research is useful for observing the effectiveness of online learning methods in practicum activities at the Faculty of Medicine, Indonesian Muslim University. This study used a quantitative method with a cross-sectional study design. From the research findings on the online laboratory practicum variable, 179 respondents (67.5%) had good practicum results, and 34 respondents (12.8%) had very good criteria. On the variable effectiveness of online practicum, the practicum results obtained with effective criteria were 86 respondents (32.5%), and very effective criteria were 66 respondents (24.9%). In the online practicum exam score variable, which has a passing threshold value, namely 61 people (23.0%) B grades, 40 B+ grades (15.1%), 26 A- grades (9.8%) and 4 A grades (1.5%). The conclusion in this study is that there is significant effectiveness in online learning methods in practicum activities at the Faculty of Medicine, Muslim University of Indonesia for students and in terms of the results of student practicum exams, evidenced by p values of 0.009 and 0.007 (p <0.05).